Pengaruh Teknik Bola Persalinan (Brithing Ball) Terhadap Penurunan Bagian Bawah Janin Pada Ibu Primigravida Inpartu Kala I Fase Aktif RSUD M.M. Dunda Limboto - Lamuda, Verawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The cause of complications in labor is labor that lasts more than 24 hours in primigravida. Other efforts to prevent prolonged labor such as the Birthing Ball which supports labor so that it can proceed physiologically. The aim of this research is to analyze the influence of the Birthing Ball Technique on lowering of the lower part of the fetus in first-stage primigravida mothers in the active phase in the delivery room at RSUD M.M. Dunda Limboto . Methods: The research method used is a quasi-experimental design with a pre-post test group design approach. The sample in this study was primigravida mothers in partu during the first stage who were active in the delivery room at RSUD M.M. Dunda Limboto, totaling 15 respondents. Results: The results of the research showed that parametric and non-parametric statistical results showed that there was a significant change in the lowering of the lower part of the fetus in the 15 respondents which could be seen with a P-Value = 0.000 < 0.05. Conclusion: There is a significant effect after carrying out the Birthing Ball Technique on primigravida mothers in the first stage of active phase.